Afterword: The Sensory Revolution Comes of Age. Issue 2 (1st September 2021) - Howes, David
Abstract: The sensory turn and the affective turn in contemporary scholarship both crystalised at roughly the same time but then diverged. This special issue reintegrates them. Conjointly, these twin approaches direct attention to the multiplicity, agency, and interactivity of the full spectrum of human faculties (i.e., how the senses and affects intersect with and may also disrupt the rule of reason) in addition to highlighting the extent to which 'the perceptual is political.' The resulting paradigm has precipitated a shift from the study of communities as 'imagined' to how they are sensed and/or felt, and from a focus on 'the human condition' to the intensive investigation of the multiple 'national post-revolutionary conditions' that define the current conjuncture. By foregrounding the aesthetics of politics, and tracking the eruption of dis-sensus (laughter, graffiti, dissent) within the con-sensus that states seek to foster in their citizenry, this special issue sounds a much-needed wake-up call.